2020
DOI: 10.1016/j.heliyon.2020.e05038
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a full-scale constructed wetland to treat greywater from tourism in Suluban Uluwatu Beach, Bali, Indonesia

Abstract: This original research examines a full-scale subsurface Constructed Wetland (CW) system in Indonesia, where most CW research has been limited to laboratory scale experiments. The CW system was located in Bali and built in 2015 in a single series formation. This study aims to demonstrate the performance of the system in treating greywater and examine the nutrient content plants’ above-ground biomass. The CW was arranged in linear sequence composed of one unplanted (CW1) and five planted treatments of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 44 publications
0
16
0
1
Order By: Relevance
“…Perdana et al (2020) cited the decay of plant organs inside constructed wetland systems and a low hydraulic retention time (HRT) as the primary causes of the negative BOD and COD removal. Plant residues in the substrate increased the organics loading in the facility, whereas inadequate contact times limited the anaerobic conditions within the media [44]. Negative removal rates of nutrients were also reported in the constructed wetlands studied by Land et al (2016).…”
Section: Emc Of Pollutants In Constructed Wetland Influent and Effluentmentioning
confidence: 85%
“…Perdana et al (2020) cited the decay of plant organs inside constructed wetland systems and a low hydraulic retention time (HRT) as the primary causes of the negative BOD and COD removal. Plant residues in the substrate increased the organics loading in the facility, whereas inadequate contact times limited the anaerobic conditions within the media [44]. Negative removal rates of nutrients were also reported in the constructed wetlands studied by Land et al (2016).…”
Section: Emc Of Pollutants In Constructed Wetland Influent and Effluentmentioning
confidence: 85%
“…This result was in line with Zhu et al (2013) which reported that phosphorus removal efficiency ranged from 78 to 84% using a medium consisting of four layers; 10cm of gravel placed at the bottom, followed by 10 cm of cinder, 12cm of ceramsite and 6cm of sand on the top and planted with Canna indica L. Meanwhile, Li et al (2013) obtained 85 % phosphorus removal efficiency using water quenched slag (WQS) media planted with Canna indica L when loaded with domestic sewage. Perdana et al (2020) reported that this value reached 91% using gravel media planted with several plants. J o zwiakowski et al ( 2017) obtained a phosphorus removal efficiency of 97 % using different particle sizes with diameter 5-10mm of carbonate-silica rock media.…”
Section: Removal Of Phosphorusmentioning
confidence: 99%
“…The results are tabulated in Tables 1 and 2. The removal e ciency of the BOD, COD, and TN has been calculated from the above results by using an equation that is Where Cin (mg/L) is the inlet concentration and Cout (mg/L) is the outlet concentration (Perdana 2020). The percentage of removal e ciency is tabulated in Tables 3 and 4.…”
Section: Characteristics Of Raw and Treated Greywatermentioning
confidence: 99%